2003
DOI: 10.1034/j.1600-0463.2003.1110410.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year follow‐up of Helicobacter pylori infection in C57BL/6 and Balb/cA mice

Abstract: Helicobacter pylori infection is associated with chronic gastritis, peptic ulcer disease, gastric adenocarcinoma and MALT lymphoma. We previously found high‐grade lymphoma after 13 months' H. pylori infection in C57BL/6 mice. In this study we followed H. pylori infection by three different isolates in C57BL/6 and Balb/cA mice for 23 months. Six‐week‐old C57BL/6 and Balb/cA mice were infected with H. pylori strains 119p (CagA+, VacA+), SS1 (CagA+, VacA+) and G50 (CagA‐, VacA‐). Mice were followed at 2 weeks, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 43 publications
3
38
1
Order By: Relevance
“…In contrast with these studies, other authors have demonstrated that the clinical outcome of H. pylori infection is independent of cagA and vacA expression in humans (Yamaoka et al, 1999) as well as in mice (Ayraud et al, 2002;Wang et al, 2003). Our data confirm these findings as the strain we used in our model was confirmed as cagA + and vacA + by PCR, and inoculated animals did not develop marked gastritis or peptic ulcers.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast with these studies, other authors have demonstrated that the clinical outcome of H. pylori infection is independent of cagA and vacA expression in humans (Yamaoka et al, 1999) as well as in mice (Ayraud et al, 2002;Wang et al, 2003). Our data confirm these findings as the strain we used in our model was confirmed as cagA + and vacA + by PCR, and inoculated animals did not develop marked gastritis or peptic ulcers.…”
Section: Discussionsupporting
confidence: 86%
“…This may be related to the pathogenesis of MALT lymphoma in humans by chronic H. pylori colonization (41). The results may also be remarkable in that a previous study observed no MALT lymphoma formation in WT mice infected with H. pylori Sydney strain 1 even after the 2-year follow-up period (42). Thus, Gal3-deficient mice may provide a useful model for the study of MALT lymphomagenesis by colonization with H. pylori Sydney strain 1 (43,44).…”
Section: Discussionmentioning
confidence: 54%
“…69,70 In a generated CagA transgenic mouse model, Ohnishi et al provided direct evidence of CagA acting as a bacterial oncoprotein in the growth of HP-related DLBCL through a tyrosine phosphorylation-dependent SHP-2-ERK signaling pathway. 71 Using in vitro B-cell line models, we and other investigators have demonstrated that translocated CagA can stimulate proliferation and restrain the apoptosis of B cells through ERK activation, BAD phosphorylation, p53 accumulation, BAD phosphorylation, or upregulation of Bcl-2 and Bcl-XL expression.…”
Section: Discussionmentioning
confidence: 99%